PENGEMBANGAN BOOKLET BUDAYA ANDHÂP ASOR BERBASIS KERATON SUMENEP PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Istiqomaturrobiah, Asri; Sudi Pratikno, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a learning resource in the form of an Andhāp Asor cultural booklet based on the Sumenep Palace for the Pancasila Education subject in the fourth grade of elementary school. This study was motivated by the lack of contextual learning resources and the decline in students’ polite behavior. The Andhāp Asor culture, as a local wisdom of Madura, is important to introduce from an early age because it embodies the values of humility, respect, and politeness. The method used is Research and Development (R&D) with the 4D model (define, design, develop, disseminate). The research subjects included fourth-grade students at SDN Daramista II and expert validators. Data were collected through observation, interviews, questionnaires, and expert validation. The results showed that the expert validation of the material achieved a 95% rating (very good), student response was 88% (very interested), and teacher response was 87.5% (very good). Thus, the Andhāp Asor culture booklet based on the Sumenep Palace is suitable for use as a learning medium and is capable of increasing students’ interest in learning and their understanding of local cultural values.